Glagolske naslonke v naslonskem nizu v slovenskih narečjih - Gromova, Maria (Jezik in slovstvo, 2025)
The article deals with four phenomena of Slovenian dialect word order. Two of them are archaic – the clitic bi and the present forms of the verb biti at the end of clitic clusters. Two other phenomena more consistently than the modern standard Slovenian language reflect the common South Slavic Slavic verb clitics’ tendency to climb to the left border of the cluster. These are the Praes.3Sg and Fut forms of the verb biti at the beginning of the cluster. Records of spontaneous dialect speech in a total range of 2,505 pages from 107 scientific works and syntactically reliable books of the Glasovi collection are analyzed. Each one of the four phenomena is illustrated with a map. The maps contain 288 points that cover 452 settlements of the Slovene language space, ie. Slovenia and Slovenians abroad in all neighboring countries. The criteria for the selection of dialect material are confirmed syntactic correctness (ie. absence of a “literary” adaptation), prose nature of the text and its accessibility. Because of this density of the material is uneven. As can be seen from the maps, both archaic phenomena are most preserved in the Littoral dialects, but their areas do not match. Although it would seem logical that innovative and archaic phenomena should not appear in the same territory, a complex combination of factors leads to the fact that both innovative and both archaic phenomena are found in the same points in the south of the Inner Carniolan dialect.
Keywords: besedni red; clitic cluster; clitics; dialect syntax; dialectology; dialektologija; narečna skladnja; naslonke; naslonski niz; skladnja; Slovenian dialects; Slovenian language; slovenska narečja; slovenščina; syntax; word orde